Mind the gap: bringing adolescents and young adults and emotional resilience into climate action - Kohli, Anjalee; Igras, Susan; Ramirez, Lacey (Frontiers in Climate, 2025)
Young people around the world are experiencing a range of emotional responses to the climate crisis. While many are organizing for action, most policies and programs addressing climate change do not consider their mental wellbeing or include them as active participants in climate decision making. In this perspective, we present a case for (1) the importance of youth’s eco-emotions in the face of climate change and their desire to be engaged in climate-related actions; and (2) the value of evidence-based public health frameworks to support building young people’s emotional resilience and integrating them into climate responses. Drawing from two recent scoping reviews and our experience in youth-centered public health programs, we describe how eco-emotions, such as eco-anxiety, eco-trauma, grief, and hope, are being experienced by adolescents and young adults. These emotions can be intense, but they also hold the potential to motivate action and connection. Our review of global climate resilience policies shows that emotional resilience is rarely addressed, and young people are largely absent from these plans. We make the case for using existing public health frameworks like Positive Youth Development (PYD) and Social Emotional Learning (SEL) to support youth mental wellness and resilience in climate programming. These approaches are already used in health and education and can be adapted to climate efforts to build young people’s emotional skills, agency, and engagement. Finally, we describe types of low-cost, evidence-based interventions that can be added to existing programs in ways that are community-based, non-clinical, and culturally appropriate. These offer a starting point for rethinking climate action as something that must include young people and their emotional well-being.